CREDIT CARD FRAUD DETECTION AND ANALYSIS USING MACHINE LEARNING ALGORITHMS - Vodala Chakshu; G. Sai Chand (International Journal of Innovations in Engineering Research and Technology, 2021)
Increase in the number of customers since last decade for credit card usage. The customer’s without prior approval many frauds have been detected. The unethical use of credit cards by hackers or credit cards users unwilling to pay back the amount are known as the major credit card frauds. The credit card transactions should be detected earlier by statistical methods if any fraud has been detected. The various algorithms in the machine learning are used to analyze the patterns and frauds. This helps the bank to eliminate the frauds by declining suspected transactions.